Behavioural validity of driving simulators for prototype HMI evaluation. Issue 6 (16th April 2020) - Spyridakos, Panagiotis D.; Merat, Natasha; Boer, Erwin R.; Markkula, Gustav M.
Abstract : In‐vehicle interfaces are now part of the vast majority of production vehicles. Such interfaces need to be thoroughly evaluated to ensure they do not pose any risks to the drivers using them. Driving simulators have extensively been used in such a context, yet their reliability in terms of how realistic a driving behaviour they elicit is still in question. An investigation on driving simulator behavioural validity in the context of prototype human–machine interface evaluation is presented in this study. Using data collected in a dual setting driving study (driving simulator and real world), as well as results from existing related literature, a comparison between driving behaviour in different types of driving simulators and in reality was carried out, for a variety of behavioural metrics. The results are presented in the form of a 'validity matrix' that aggregates the level of behavioural validity different simulator settings can achieve for different behavioural metrics.